2016
DOI: 10.1007/978-3-319-26974-0_9
|View full text |Cite
|
Sign up to set email alerts
|

On the Roles of the Transient Receptor Potential Canonical 3 (TRPC3) Channel in Endothelium and Macrophages: Implications in Atherosclerosis

Abstract: In the cardiovascular and hematopoietic systems the Transient Receptor Potential Canonical 3 (TRPC3) channel has a well-recognized role in a number of signaling mechanisms that impact the function of diverse cells and tissues in physiology and disease. The latter includes, but is not limited to, molecular and cellular mechanisms associated to the pathogenesis of cardiac hypertrophy, hypertension and endothelial dysfunction. Despite several of these functions being closely related to atherorelevant mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…TRPCs have been proved to be involved in the pathogenesis of cardiovascular diseases, such as essential hypertension, cardiac hypertrophy, intima hyperplasia and endothelial dysfunction, and atherosclerosis [ 37 ]. TRPC3 has been documented to be implicated in atherosclerosis through regulating endothelium and macrophages [ 38 ]. A previous study demonstrated that TRPC3 had a dual beneficial effect on lesion progression by reducing cellularity at early stages and necrosis in the advanced plaques in apoe −/− mouse model [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRPCs have been proved to be involved in the pathogenesis of cardiovascular diseases, such as essential hypertension, cardiac hypertrophy, intima hyperplasia and endothelial dysfunction, and atherosclerosis [ 37 ]. TRPC3 has been documented to be implicated in atherosclerosis through regulating endothelium and macrophages [ 38 ]. A previous study demonstrated that TRPC3 had a dual beneficial effect on lesion progression by reducing cellularity at early stages and necrosis in the advanced plaques in apoe −/− mouse model [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TRPC3 shows its impact on endothelial dysfunction and is responsible for causing apoptosis of macrophages related to the pathogenesis of atherosclerosis. The relevance of TRPC3 with atherosclerosis has also been verified by in vivo studies [ 60 ], where the process is associated with endoplasmic reticulum stress that is considered the primary mechanism of cell apoptosis in atherosclerotic plaques [ 61 ]. It is well known that endothelial barrier function dysfunction is regarded as a leading cause of atherosclerotic plaque formation.…”
Section: Pathological Roles Of Store-operated Channels In Cardiovascu...mentioning
confidence: 99%
“…Inactivating FLNA in mice models also led to impaired macrophage signaling and function, accompanied by reduced atherosclerosis [ 100 ]. Transient receptor potential canonical 3 (TRPC3) in macrophages has been linked with various mechanisms in atherosclerosis disease progression [ 104 ]. In novel studies, mice with a macrophage-specific deficiency of transient receptor potential canonical 3 (TRPC3) displayed reduced stress-induced apoptosis, necrosis, and calcification in advanced atherosclerotic plaque [ 105 , 106 , 107 ].…”
Section: Macrophages and Atherosclerosismentioning
confidence: 99%